The Kindergarten Teachers’ Pedagogical Competences: A Case Study - MUHAMAD TARIDI; AMRIN DONO (Indonesian Research Journal in Education |IRJE|, 2019)
The study aimed to find out the pedagogical competence of teachers to carry out the interactions of the teaching and learning processes and to assess the development of the cognitive aspects of the children in one Indonesian kindergarten. This study used a qualitative method with the case study tradition. We highlighted the analysis of the data through transcription, coding, and thematic analyses. Findings of the study focused on three major themes including teachers’ competence for planning teaching and learning programs (planning activities for teaching and learning processes and care and protection programs), teacher competence in implementing interaction or managing teaching and learning processes (learning from various resources and doing evaluation on the method used in teaching), and teachers’ competence for conducting learning assessment and evaluation (test assessment and evaluation and non-test assessment and evaluation). Some recommendations for the betterment of Indonesian kindergarten education are proposed.